PENINGKATAN KINERJA GURU MELALUI SUPERVISI DI SMKN 8 PEKANBARU TAHUN PELAJARAN 2021/2022 - MARSEFEL MARSEFEL (JURNAL ILMIAH SIMANTEK, 2022)
The existence of supervisors in the world of education has an important role in fostering and selecting teachers. A similar fact also occurred at SMKN 8 Pekanbaru. Based on observations, the average value of summative tests (end of semester), formative test scores (daily tests) decreased. There are many possible factors that cause low student achievement, one of which is decreased teacher performance. The purpose of this research is that this research can improve the quality of learning in SMKN, through the creation and use of methods in accordance with the existing curriculum directions. By improving teacher performance it is expected to increase student achievement. With the supervision of the madrasah head can improve teacher performance in the learning process. The type of research used in this research is the school action research method (PTS). The research location was carried out at SMKN 8 Pekanbaru. When the research was carried out in September 2021. The subjects of the action research were 24 teachers at SMKN 8 Pekanbaru. The technique of collecting data from this school action research is through quantitative data obtained from observation and interviews. The data analysis technique used in this research is quantitative data analysis originating from the acquisition of the instrument. The results of this study indicate that with this research there is an increase in student achievement in the learning process. There is an increase where students are more active in the learning process. Increased teacher performance in the learning process, namely from the first cycle 74.3% increased in the second cycle 80.04% Good category (B). Improving the quality of education at SMKN 8 Pekanbaru in 2021/2022